AMPylation of small GTPases by Fic enzymes. Issue 6 (27th October 2022) - Gulen, Burak; Casey, Amanda; Orth, Kim
Abstract : Small GTPases orchestrate numerous cellular pathways, acting as molecular switches and regulatory hubs to transmit molecular signals and because of this, they are often the target of pathogens. During infection, pathogens manipulate host cellular networks using post‐translational modifications (PTMs). AMPylation, the modification of proteins with AMP, has been identified as a common PTM utilized by pathogens to hijack GTPase signalling during infection. AMPylation is primarily carried out by enzymes with a filamentation induced by cyclic‐AMP (Fic) domain. Modification of small GTPases by AMP renders GTPases impervious to upstream regulatory inputs, resulting in unregulated downstream effector outputs for host cellular processes. Here, we overview Fic‐mediated AMPylation of small GTPases by pathogens and other related PTMs catalysed by Fic enzymes on GTPases. Abstract : AMPylation, the modification of proteins with AMP, is a post‐translational modification that pathogens often utilize to hijack GTPase signalling during infection. AMPylation is primarily carried out by enzymes with a filamentation induced by cyclic‐AMP (Fic) domain. Modification of small GTPases by AMP renders GTPases impervious to upstream regulatory inputs, resulting in unregulated downstream effector outputs for host cellular processes.